Hubungan Antara Penilaian Anak Terhadap Cerita Film Anak di Televisi dengan Kemampuan Empati Pada Anak Usia Sekolah Dasar - Sesotya Wedadjati, Ratna (Unisia, 2012)
This research aims at examining a correlation between judgment of children film on television and empathy ability. Samples of this research are ninety three (N=93) children of elementary school, age between nine to twelve years old in SDN Ngetal Sleman. Instruments used are judgment of children film on television and empathy ability scales. Data are analyzed using the correlation analysis of product moment program based on the SPSS for Windows 13 release. Statistical test reveals that there is significant correlation between the level of judgment of children film on television and empathy ability (r=0.382; p=0.000 or p<0.01). Keywords: judgment, children film, television, empathy ability.